Pengaruh Atribut Produk Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Mixue Di Kalangan Mahasiswa Universitas 17 Agustus 1945 Semarang - Hermawan Budiyanto (Politeknik Kampar, 2023)
This study seeks to examine the impact of product attributes, product quality on purchasing decisions for purchasing Mixue products among students of the University of 17 August 1945 Semarang. This research design uses a quantitative approach. The sample was taken using stratified random sampling technique by accidental sampling which was collected through online media for students who had made purchases of Mixue products. The analysis method used is multiple linear regression analysis and hypothesis testing. The results of the study indicate that this product attribute has a positive effect on purchasing decisions, as well as product quality has a positive effect on purchasing decisions. Simultaneously, both product attributes and product quality together have a positive effect on purchasing decisions for Mixue Products among students at the University of 17 August 1945 Semarang